Analysis of Hemodialysis Unit Costs Using the Double Distribution Approach to Enhance Hospital Profitability: A Case Study at YARSI Hospital in Jakarta, Indonesia - Wendi Pradiyatmoko; Hulmansyah; Laura Mayanda; Dicky Budiman; Misbahul Munir; Danial Rasyid (International Journal of Advanced Health Science and Technology, 2025)
Chronic Kidney Disease (CKD) represents a major and growing health challenge globally and in Indonesia, with the number of patients requiring hemodialysis increasing sharply in recent years. This surge in demand places significant financial pressure on healthcare institutions, necessitating precise cost management to maintain service quality and hospital sustainability. This study aims to calculate the actual unit cost of hemodialysis at YARSI Hospital using the Double Distribution (DD) method, which provides a transparent allocation of both direct and indirect costs. Employing a quantitative descriptive case study design, data were collected from hospital financial records and service documentation for 16,789 hemodialysis sessions conducted during 2024. The DD method was applied in two stages: distributing overhead costs to intermediate cost centers, and subsequently distributing intermediate costs such as those related to pharmacy, laboratory, and medical personnel to final service centers. The analysis revealed that the unit cost of Single-Use hemodialysis was IDR 1,927,643, while Re-Use hemodialysis was IDR 1,956,284. The minimal difference between the two systems indicates that high utilization volume significantly influences cost efficiency. These findings confirm that the DD method enables hospitals to obtain a more accurate understanding of cost structures, thereby supporting evidence-based decision-making in pricing and resource management. In conclusion, implementing the Double Distribution approach can enhance cost transparency, optimize efficiency, and guide hospitals in establishing rational service rates without compromising care quality. Future research should involve multi-hospital comparisons to strengthen the generalizability of cost-efficiency models in hemodialysis services.